2015
DOI: 10.1155/2015/152616
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume and Splenomegaly as Useful Markers of Subclinical Activity in Egyptian Children with Familial Mediterranean Fever: A Cross-Sectional Study

Abstract: Objective. To study whether mean platelet volume (MPV) and splenomegaly could be used as subclinical inflammatory markers in children with familial Mediterranean fever (FMF) at the attack-free period. Patients and Methods. The study included ninety-seven children with FMF. MPV was carried out within 4 hours of blood sampling according to standard laboratory practice. Splenomegaly was determined by abdominal ultrasound (USG). Results. High MPV was detected in 84.45% of our studied patients and was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It is frequently found to be decreased in the presence of active high grade inflammation; that is, active phase of RA, AS, ulcerative colitis and Chron disease [ 27 , 41 , 42 ] activation of systemic lupus erythematosus (SLE) arthritis [ 43 ] and active SLE. [ 44 ] Increased MPV levels were on the other hand mainly found in states of low grade inflammation such as: cellulitis, [ 45 ] idiopathic subjective tinnitus, [ 46 ] symptom/attack-free periods of familial Mediterranean fever patients [ 47 , 48 ] and irritable bowel syndrome, [ 49 ] obstructive sleep apnea syndrome. [ 50 ] Being a state of low grade systemic inflammation, OA, is also expected to be associated with higher levels of MPV and this is demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently found to be decreased in the presence of active high grade inflammation; that is, active phase of RA, AS, ulcerative colitis and Chron disease [ 27 , 41 , 42 ] activation of systemic lupus erythematosus (SLE) arthritis [ 43 ] and active SLE. [ 44 ] Increased MPV levels were on the other hand mainly found in states of low grade inflammation such as: cellulitis, [ 45 ] idiopathic subjective tinnitus, [ 46 ] symptom/attack-free periods of familial Mediterranean fever patients [ 47 , 48 ] and irritable bowel syndrome, [ 49 ] obstructive sleep apnea syndrome. [ 50 ] Being a state of low grade systemic inflammation, OA, is also expected to be associated with higher levels of MPV and this is demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A significant correlation was evident between thrombocyte activation and splenomegaly in FMF children in remission. The mean platelet volume, which reflects platelet function and activation, was higher in FMF patients (16).…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Ozkayar et al reported that FMF patients without AA had significantly higher MPV level compared to the control group [19]. In 2015, Marzouk and colleagues found that 84% of the patients with FMF had high MPV levels and they proposed that MPV values may be used as useful markers of subclinical activity in Egyptian children with FMF [17].…”
Section: Discussionmentioning
confidence: 99%
“…Due to these relationships between inflammatory activity and MPV value, MPV has been suggested by many to be a marker of inflammatory activity in various diseases [9,15,16]. The MPV levels in FMF have been previously studied [17]. However, whether MPV levels in FMF patients are lower or higher compared to healthy subjects remains as a topic of ongoing debate.…”
Section: Introductionmentioning
confidence: 99%